Corporate Social Responsibility as an Entrance to Risk and Crisis Management "An Appraisal Study for Zain Telecommunications Corporation" - زياني, خولة (Milev Journal of Research and Studies, 2020)
This study aims to identify the role of corporate social responsibility in managing risks and crises, as corporate social responsibility expresses a proactive way to avoid potential risks and crises in the activities of institutions, and the experience of Zain Telecom in this field has been highlighted, as the latter works to adhere to adopting the principles of responsibility Social Development in all its activities, and it constantly seeks to apply responsible and sustainable practices, which leads to avoiding crises, improving risk management practices, establishing a governance environment that contributes to building constructive relationships with stakeholders and governments, creates a safe environment for the group's work and improves the practices of its departments.